-2y = 4 - y - 3
y - 2y = 4 - 3
y * (1 - 2) = 4-3
y = (4-3) / (1-2)
y = 1/-1
y = -1
2007-01-25 07:43:31
·
answer #1
·
answered by haxxormaster 2
·
0⤊
0⤋
3 - 2y = 4 - y
3 = 4 + y Add 2y to both sides
-1 = y Subtract 4 from both sides
y = -1
Check:
3 - 2(-1) = 4 - (-1)
3 + 2 = 4 + 1
5 = 5 Check!
2007-01-25 07:45:08
·
answer #2
·
answered by Tony O 2
·
0⤊
0⤋
3 - 2y = 4 - y
3 - 2y + y = 4 = y + y
3 - y = 4
3 - y - 3 = 4 - 3
- y = 1
-1(- y) = - 1(1)
y = - 1
The aswer is y = - 1
Inseert the y value into the equation
- - - - - - - - - - - - - - - - - - - - - - - -
Check
3 - 2y = 4 - y
3 - 2(- 1) = 4 - ( - 1)
3 - (- 2) = 4 + 1
3 + 2 = 5
5 = 5
- - - - - - - - s-
2007-01-25 08:50:49
·
answer #3
·
answered by SAMUEL D 7
·
0⤊
0⤋
y=-1
2007-01-25 07:49:56
·
answer #4
·
answered by mora_omar206 1
·
0⤊
0⤋
y= -1
2007-01-25 07:43:05
·
answer #5
·
answered by Anonymous
·
0⤊
0⤋
3 - 2y = 4 - y
add 2y to both sides
3 = 4 + y
subtract 4 from both sides
-1 = y
2007-01-25 07:43:05
·
answer #6
·
answered by bequalming 5
·
0⤊
0⤋
3-2y= 4-y
Collect all like terms together
3-2y-4+y=0
3-2y+y-4=0
3-y-4=0
-1-y=0
-1=y
y=-1
Btw why do we have to do your homework little junior?
2007-01-25 07:50:23
·
answer #7
·
answered by MK <>< 5
·
0⤊
0⤋
3-2y=4-y
3-4=-y+2y
-1=y
2007-01-27 13:40:06
·
answer #8
·
answered by shirley_hbuk 1
·
0⤊
0⤋
3 = 4 - y + 2y
3 = 4 + y
3 - 4 = y
y = - 1
2007-01-25 09:11:00
·
answer #9
·
answered by Como 7
·
0⤊
0⤋
3-2y=4-y
take all y values onto same side
-2y+y=4-3
-y=1
y=-1
2007-01-25 07:49:29
·
answer #10
·
answered by missree 5
·
0⤊
0⤋